2023
DOI: 10.3390/molecules28031483
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of Extra Virgin Olive Oils of Turkish Olive Cultivars

Abstract: Extra virgin olive oils (EVOOs) obtained from five Turkish olive cultivars widely produced in the Aegean and Marmara regions were investigated based on their total antioxidant capacity (TAC), total phenolic content (TPC), pigment contents, fatty acid (FA) profiles, phenolic compounds (PC), volatile compounds (VC), and sensory properties. The results showed that all properties of EVOO samples were significantly affected by the olive cultivar used. The pigment contents in Ayvalık (9.90 mg·kg−1) and Uslu (9.00 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 58 publications
5
3
0
Order By: Relevance
“…This clearly explains the difference between HPLC results and TPC results at Table 4. Our results are consistent with TPCs in Turkish olive oils ranging between 12 and 990 mg/kg of oil, as reported by (Keceli, 2013a; 2013b; Arslan & Ok, 2020; Korkmaz, 2023; Uluata et al, 2021).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This clearly explains the difference between HPLC results and TPC results at Table 4. Our results are consistent with TPCs in Turkish olive oils ranging between 12 and 990 mg/kg of oil, as reported by (Keceli, 2013a; 2013b; Arslan & Ok, 2020; Korkmaz, 2023; Uluata et al, 2021).…”
Section: Resultssupporting
confidence: 93%
“…A daily dose of 2–15 mg of hydroxytyrosol or oleuropein‐related compounds is required for health claims made by EFSA (European Commission, 2012). Our findings are consistent with the hydroxtyrosol and tyrosol contents of Turkish cultivars (Al‐Juhaimi et al, 2017; Arslan & Ozcan, 2011; Korkmaz, 2023; Uluata et al, 2021) and some Spanish and Tunisian cultivars reported by (El‐Gharbi et al, 2018; Polari et al, 2021). On the other hand, changes in environmental conditions (increase in temperature and relative humidity and decrease in rainfall see Table 1) may have increased both tyrosol and p‐coumaric acid levels significantly in Gemlik virgin olive oils in 2017 harvest year (Table 4).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As seen in Table 2, the coumaric acid content of the KK group was found to be significantly higher than the other groups (p < 0.05). Similar to these results, Korkmaz [34] reported that regional differences in phenolics of different varieties from olive oils obtained from different regions of Turkey appeared to be distinctive in PCA analysis. ES samples were clustered in a different position from the other sample groups in the score plot, with PC2 in the positive and PC1 in the negative part of the score plot.…”
Section: Phenolic Profiles Of Samplessupporting
confidence: 74%